Inteins as indicators of gene flow in the halobacteria - Soucy, Shannon M.; Fullmer, Matthew S.; Papke, R. Thane; Gogarten, Johann Peter (Frontiers in Microbiology, 2014)
This research uses inteins, a type of mobile genetic element, to infer patterns of gene transfer within the Halobacteria. We surveyed one hundred and eighteen genomes representing twenty-six genera of Halobacteria for intein sequences. We then used the presence-absence profile, sequence similarity and phylogenies from the inteins recovered to explore how intein distribution can provide insight on the dynamics of gene flow between closely related and divergent organisms. We identified twenty-four proteins in the Halobacteria that have been invaded by inteins at some point in their evolutionary history, including two proteins not previously reported to contain an intein. Furthermore, the size of an intein is used as a heuristic for the phase of the intein’s life cycle. Larger size inteins are assumed to be the canonical two domain inteins, consisting of self-splicing and homing endonuclease domains (HEN); smaller sizes are assumed to have lost the HEN domain. For many halobacterial groups the consensus phylogenetic signal derived from intein sequences is compatible with vertical inheritance or with a strong gene transfer bias creating these clusters. Regardless, the coexistence of intein-free and intein-containing alleles reveal ongoing transfer and loss of inteins within these groups. Inteins were frequently shared with other Euryarchaeota and among the Bacteria, with members of the Cyanobacteria (Cyanothece, Anabaena), Bacteriodetes (Salinibacter), Betaproteobacteria (Delftia, Acidovorax), Firmicutes (Halanaerobium), Actinobacteria (Longispora), and Deinococcus-Thermus-group.